2016
DOI: 10.1016/j.chemosphere.2016.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Pollution evaluation in the Shahrood River: Do physico-chemical and macroinvertebrate-based indices indicate same responses to anthropogenic activities?

Abstract: This study evaluates the impact of anthropogenic activities on the Shahrood River using water physico-chemical variables and macroinvertebrates data sets obtained over a period of 12 months between February 2012 and February 2013 at 8 sampling sites. Biotic indices i.e. FBI and BMWP based on macroinvertebrates and physico-chemical indices (MPI, HPI and NSF-WQI) were employed to evaluate the water quality status in connection with natural- and human-induced pressures. Based on physico-chemical indices, water qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…However, these families are considered resistant and resilient taxa due to the anthropogenic pressure that impoverish biological communities and consequently alter aquatic ecosystems [35] [36]. These results could be related to the hydrological stability and physicochemical quality of water [37]. In addition, they coincide with the results of Verdonschot et al (2012) [38] and [39], who indicate that in areas with a temperate climate, seasonality plays a very important role in the structure of macroinvertebrate communities.…”
Section: Variation Patterns Of Benthic Macroinvertebrate Communitiessupporting
confidence: 62%
“…However, these families are considered resistant and resilient taxa due to the anthropogenic pressure that impoverish biological communities and consequently alter aquatic ecosystems [35] [36]. These results could be related to the hydrological stability and physicochemical quality of water [37]. In addition, they coincide with the results of Verdonschot et al (2012) [38] and [39], who indicate that in areas with a temperate climate, seasonality plays a very important role in the structure of macroinvertebrate communities.…”
Section: Variation Patterns Of Benthic Macroinvertebrate Communitiessupporting
confidence: 62%
“…Only one parameter that is under the standard that is dissolved oxygen (DO). DO becomes a limiting factor in the waters which is a chemical indicator of pollution (Sharifinia et al, 2016). The lower value of DO will show the condition toward anoxia which is related to the declination of oxygen penetration to the water.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that using biotic indices based on family level provides sufficient information to assess the biological water quality [29][30][31][32]. It has been shown that macroinvertebrate-based indices better reflect water quality conditions compared to physical-chemical based indices [33]. Therefore, the biotic macroinvertebrate index BMWP-Colombia (Biological Monitoring Working Party-Colombia) was calculated according to the modified method proposed by Zuniga and Cardona (2009).…”
Section: Sampling and Assessment Methodsmentioning
confidence: 99%
“…Each macroinvertebrate taxon received a score that reflects its susceptibility to pollution, where pollution-intolerant taxa receive high scores, whereas pollution-tolerant taxa were given low scores [34]. The total score for each site indicated the water quality, with categories ranging from very bad (0-15), bad (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), poor , moderate (61-100) to good (>100).…”
Section: Sampling and Assessment Methodsmentioning
confidence: 99%